Integrating biological data with substrate and bathymetric information in MPAs in of oceanic islands - Álvaro, Nuno V. (2013)
World Conference in Marine Biodiversity (Panel Marine Protected Areas: a Sea Change in Perception, Policy and Law), Aberdeen, Scotland (UK), 26-30 de Setembro 2011.